Viral Marketing dan Asosiasi Brand dengan Boneka Labubu - Diorra Calysta Wijaya; Miracle Angel Yosie Rogi (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research explores the impact of viral marketing and brand associations that leverage the Labubu doll as a promotional tool. Many brands capitalize on the doll’s popularity to attract consumers, making it a fascinating case study for marketing strategies. Using a qualitative approach, this study gathered data through a Focus Group Discussion (FGD) with six participants who have relevant experience in the topic. The findings highlight that marketing strategies, particularly the